The Post-Socialist Internet - Bareikyte, Migle (transcript Verlag, 2024)
How is the Internet produced as an infrastructure in post-socialist Lithuania? Migle Bareikyte contributes to the growing field of STS and media studies with a distinct focus on Eastern Europe. She situates the Internet development in Lithuania's telecom industry with the exploration of its labor practices, geopolitical imaginaries, and critical negotiations from a bottom-up perspective. Bareikyte further explores how fieldwork-based research can foster new theorizations of media infrastructures. Finally, she argues for a situated investigation of new places and actors beyond the United States and Western Europe-such as post-socialist regions-in order to explore the diversity of media infrastructures.